Prediction of Corporate Takeover: An Empirical Studies On Malaysian Firm - Fauzias Mat Nor; Mariah Sheikh Hussin (Asian Academy of Management Journal, 1998)
Prediction of Corporate Takeover: An Empirical Studies On Malaysian Firm (PDF not available)